DYNAMIC CHARACTERISTICS OF OPERATOR`S “VISUAL CHANNEL” WHILE WORKING WITH TFT MONITOR - Petrova, Yulia (Proceedings of National Aviation University (archive), 2014)
Experimental models of the dynamics of the human-operators “visual channel” are constructed while operators working with thin-film transistor monitor and stochastic information processing.